2022
DOI: 10.5812/ijem-120949
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Subclinical Hyperthyroidism and Adverse Pregnancy Outcomes: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Context: Findings from studies evaluating adverse pregnancy outcomes in pregnant women with subclinical hyperthyroidism are conflicting and inconclusive. Objectives: In this systematic review and meta-analysis, our aim was to evaluatethe pooled odds ratio (OR) of adverse pregnancy outcomes in women with subclinical hyperthyroidism, compared to euthyroid women. Data Sources: Scopus, PubMed (including Medline), and Web of Science databases were systemically searched for regaining published studies to January 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The relationship between subclinical hyperthyroidism and poor outcomes is less clear. While one study reported an increased risk of preeclampsia but not spontaneous abortion [ 138 ], a systematic review identified no increased risk for poor outcomes [ 197 , 214 ].…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%
“…The relationship between subclinical hyperthyroidism and poor outcomes is less clear. While one study reported an increased risk of preeclampsia but not spontaneous abortion [ 138 ], a systematic review identified no increased risk for poor outcomes [ 197 , 214 ].…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%
“…GHT results in an imbalance in the concentration of circulating thyroid-stimulating hormone (TSH), T3, and T4, leading to insufficient levels of thyroid hormones [ 7 ]. This condition is associated with adverse maternal outcomes such as preeclampsia and gestational diabetes [ 8 , 9 ], as well as detrimental effects on offspring, including low birth weight and impaired neuro-cognitive development, which can manifest as attention deficit hyperactivity disorder and autism [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%